2008
DOI: 10.1161/hypertensionaha.108.118315
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Different Measures of Blood Pressure and Coronary Artery Calcium in Postmenopausal Women

Abstract: Abstract-The aim of this study was to determine the magnitude and significance of the associations among coronary artery calcium (CAC) and systolic blood pressure, diastolic blood pressure, pulse pressure, and mean arterial pressure. Women 50 to 59 years of age at baseline in the Women's Health Initiative clinical trial of conjugated equine estrogen underwent computed tomography scanning of the chest after the end of the trial. Blood pressures were measured twice with the participant in the seated position usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In addition, systolic blood pressure, high-density lipoproteins, fasting blood glucose, and eGFR were also found to be significantly associated with high CAC. Previous studies showed that high systolic blood pressure is associated with CAC, as well as with the risk of coronary and cardiovascular events [ 21 , 22 ]. Patients with subclinical atherosclerosis, as determined by CAC scores, reportedly have fewer high-density lipoprotein particles [ 23 ]; conversely, increasing levels of high-density lipoproteins were also associated with less CAC [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, systolic blood pressure, high-density lipoproteins, fasting blood glucose, and eGFR were also found to be significantly associated with high CAC. Previous studies showed that high systolic blood pressure is associated with CAC, as well as with the risk of coronary and cardiovascular events [ 21 , 22 ]. Patients with subclinical atherosclerosis, as determined by CAC scores, reportedly have fewer high-density lipoprotein particles [ 23 ]; conversely, increasing levels of high-density lipoproteins were also associated with less CAC [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior to our study, there has been only limited information on the presence of atherosclerotic calcification in non-coronary vascular beds 11. A previous study demonstrated that the detection of extra-coronary atherosclerosis, potentially helps to indentify individuals more likely to develop new calcified coronary disease 12.…”
Section: Discussionmentioning
confidence: 99%
“…Low DBP is associated with carotid stenosis in subjects with isolated systolic hypertension 9 and with coronary artery calcium in postmenopausal women. 31 Several pathophysiological mechanisms have been suggested to explain the J-shaped phenomenon. 30 Low DBP may reflect the presence of a clinical or subclinical comorbid condition (especially heart disease or cancer).…”
Section: Discussionmentioning
confidence: 99%